Use of Models of Finite Elements in the Biomechanics of the Lumbar Spine - Oppermann, Marcelo; Brasil, Lourdes Mattos; Silva, Alex Sandro Araújo; Cardoso, Leandro Xavier (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
The same correspondence between general mechanics and civil engineering is true for biomechanics and surgical implants. Currently, numerous mechanical processes are required until a prosthesis is offered to its target audience. These processes typically require human or animal vertebrae, as well as all the complexity involving such tissues, for example, an ethics committee, the availability of materials, etc. Thus, finite element models (FEMs) have become a great option to carry out biomechanical tests independently from anatomical specimens, and, at the same time, to obtain mathematical data to assist in the general physical understanding. The present review discusses the mechanical principles involved in bioengineering, clarifies the steps for the development of FEMs, and shows application scenarios for these models. To the knowledge of the authors, the present paper is the first review study in Portuguese aimed to health care professionals in a language accessible to them.
Keywords: spine; finite elements; biomechanics; pedicle screw